Preparation and Characterization of Loperamide-Loaded Dynasan 114 Solid Lipid Nanoparticles for Increased Oral Absorption In the Treatment of Diarrhea - Wei, Lili; Yang, Yunfang; Shi, Kun; Wu, Jun; Zhao, Wei; Mo, Jingxin (Frontiers in Pharmacology, 2016)
The aim of the project was to assemble two optimum solid lipid nanoparticle (SLN) formulations for oral delivery of loperamide (LPM) to treat different types of diarrhea, and to evaluate their release profiles in vitro and pharmacokinetic properties in vivo. In this work, glyceryl trimyristate (Dynasan 114) nanoparticles containing the drug LPM and sodium cholate as a stabilizer were prepared using a modified solvent evaporation technique. Two LPM-loaded SLNs, namely LPM-SLN-1 (LPM-SLN with a high ratio rate of lipid to drug) and LPM-SLN-2 (LPM-SLN with a low ratio rate of lipid to drug), were prepared by the solvent evaporation method. A change in the lipid concentration affects the characteristics of LPM-SLNs. The average sizes of the LPM-SLNs were 303 ± 18 nm and 519 ± 36 nm, separately, as analyzed by dynamic light scattering (DLS). The LPM-SLNs were found to be round with a smooth surface, as observed using a transmission electron microscope (TEM) and a scanning electron microscope (SEM). The average encapsulation efficiencies were 87 ± 3.78% w/w and 84 ± 5.17%, accordingly. In the in vitro release experiments, LPM-SLNs showed a continuous release profile of LPM without any burst release. The oral bioavailability of LPM-SLNs was analyzed using Wistar rats. The relative bioavailabilities of LPM-SLNs were 227% and 153%, respectively, as compared that of the LPM tablet. There was no difference in the Tmax between LPM-SLN-2 and the LPM tablet. In conclusion, LPM-SLN-1 significantly improved the oral bioavailability of LPM, while LPM-SLN-2 having the same swift action as the LPM tablet. These results demonstrate the potential of LPM-SLNs in the oral delivery of LPM to treat different types of diarrhea.